Représentations de la liberté : comparaison des versions française, anglaise et arabe de la chaîne transnationale France 24 - Moalla, Sonja (Gerflint, 2025)
The aim of this article is to study the ways in which freedom is addressed in the French, English and Arabic versions of the transnational channel France 24. The corpus is selected from France 24’s YouTube channels produced in the two months following the murder of Samuel Paty. In this study, discourse analysis is carried out with a focus on the syntactic environment of the word freedom. The results show that freedom is used twice as much in the English and Arabic versions compared to the French version, and that there are differences in the forms of freedom mentioned. The findings also reveal that the phrase freedom of expression in French communicates a more specific and complex idea compared to the English and Arabic languages.